Oral contraceptives and menopausal hormone therapy as breast cancer risk categories - I. V. Vуsotskaya; V. P. Letyagin; I. K. Vorotnikov; V. U. Kirsanov; I. A. Gladilina; E. A. Kim (ABV-press, 2019)
The research provided includes analysis of the current state of the problem on the use of oral contraceptives and menopausal hormone therapy. These therapeutic options were evaluated in terms of their importance for the risk of breast cancer. The possibility of using these drugs in a cohort of high-risk patients (women with family history of breast cancer) and in the group of patients with benign pathology was analyzed as well. Modern trends of menopausal hormone therapy prescription in different clinical situations were determined.